Social cognitive theory an agentic perspective on human nature - Bandura, Albert 1925-2021 (John Wiley & Sons, Inc., 2023)
"As my father's ideas progressed and the Star War films became wildly popular, he coined the phrase "May the Efficacy Force be with you". He used it as his signature phrase when signing books and wanted it inscribed on his headstone, which it is. Self-efficacy is central among the psychological constructs he posited as influencing behavior, and reflects beliefs in one's ability to master particular challenges. To wish someone the "Efficacy Force" is to hope that they are inspired to develop confidence in their ability to succeed at their life pursuits, thereby establishing a sense of control over their life course. It is a wish that they create visions of what they want to accomplish, figure out how to pursue them, and get back in the saddle when they run into trouble during their efforts. It is a wish that they take the reins of life and steer their own course"-- Provided by publisher.